Sensitivity of Electron Transfer Mediated Decay to Ion Pairing - Pohl, Marvin N; Richter, Clemens; Lugovoy, Evgeny; Seidel, Robert; Slavíček, Petr; Aziz, Emad F; Abel, Bernd; Winter, Bernd; Hergenhahn, Uwe (The journal of physical chemistry. B, 2017)
Ion pairing in electrolyte solutions remains a topic of discussion despite a long history of research. Very recently, nearest-neighbor mediated electronic de-excitation processes of core hole vacancies (electron transfer mediated decay, ETMD) were proposed to carry a spectral fingerprint of local solvation structure and in particular of contact ion pairs. Here, for the first time, we apply electron-electron coincidence detection to a liquid microjet, and record ETMD spectra of Li 1s vacancies in aqueous solutions of lithium chloride (LiCl) in direct comparison to lithium acetate (LiOAc). A change in the ETMD spectrum dependent on the electrolyte anion identity is observed for 4.5 M salt concentration. We discuss these findings within the framework of the formation and presence of contact ion pairs and the unique sensitivity of ETMD spectroscopy to ion pairing.